2012
DOI: 10.1118/1.4703901
|View full text |Cite
|
Sign up to set email alerts
|

CT based computerized identification and analysis of human airways: A review

Abstract: As one of the most prevalent chronic disorders, airway disease is a major cause of morbidity and mortality worldwide. In order to understand its underlying mechanisms and to enable assessment of therapeutic efficacy of a variety of possible interventions, noninvasive investigation of the airways in a large number of subjects is of great research interest. Due to its high resolution in temporal and spatial domains, computed tomography (CT) has been widely used in clinical practices for studying the normal and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 90 publications
(141 reference statements)
0
41
0
Order By: Relevance
“…The algorithm was able to segment bronchi beyond the eleventh-twelfth generation, overcoming the problem of segmenting and analyzing bronchi beyond the fifth generation with automatic algorithms, described by Mountadon et al 15 The proposed algorithm exploits the well established thresholding and region growing techniques. 11 Finally, the required processing time (about 2 minutes on a standard PC) is reasonable and could be further reduced by the use of a high-end computer system, allowing near real-time processing. Alternative approaches were proposed in literature, as segmentation methods based on fuzzy connectivity, 16 mirror image Gaussian fit, 17 full width at half maximum, 18 19 and use of models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm was able to segment bronchi beyond the eleventh-twelfth generation, overcoming the problem of segmenting and analyzing bronchi beyond the fifth generation with automatic algorithms, described by Mountadon et al 15 The proposed algorithm exploits the well established thresholding and region growing techniques. 11 Finally, the required processing time (about 2 minutes on a standard PC) is reasonable and could be further reduced by the use of a high-end computer system, allowing near real-time processing. Alternative approaches were proposed in literature, as segmentation methods based on fuzzy connectivity, 16 mirror image Gaussian fit, 17 full width at half maximum, 18 19 and use of models.…”
Section: Discussionmentioning
confidence: 99%
“…To use the full potential of MDCT validated, automated, and non-subjective image analysis techniques are required. Several methods have been proposed in literature as extensively described in the review from Pu et al 11 As noted by Pu, a first recognized limitation of available airway tree segmentation schemes is the miss of a large fraction of small airways. Secondly, the unavailability of a gold standard results leaded to the use of artificial phantoms with a complexity The aim of our study is to develop and validate an operatorindependent algorithm, able to perform airways segmentation and measurement including small airways.…”
Section: Introductionmentioning
confidence: 99%
“…In the bronchial research field, a review of the principal approaches can be found in (Pu et al, 2012) and (Feragen et al, 2015). A good overview of early methods is also available in (Graham and Higgins, 2006a,b) and (Metzen et al, 2007(Metzen et al, , 2009, where the authors explained, among others, why searching a graph isomorphism is not directly applicable to match anatomical trees.…”
Section: Related Workmentioning
confidence: 98%
“…[27][28][29][30][31][32] A relatively detailed description of these approaches can be found in a review article. 33 Despite the intensive efforts, available algorithms still miss a large fraction of small airways. Whereas abnormalities, such as obstruction, frequently occur in peripheral regions, and small airways always constitute a region of interest for investigating various lung diseases.…”
Section: Introductionmentioning
confidence: 99%